Impact of the “active strategies” program on the Reading literacy of undergraduate students of semester II of Pedagogy and Physical Culture - Flores Morales, Jorge Alberto (2018)
The purpose of this research was to determine the impact of the “active strategies” program on the Reading literacy of students from semester II of Pedagogía y Cultura física  Pedagogy and Physical Culture) of the University “Enrique Guzmán y Valle” 2016. This is an applied research with a quasi-experimental design. The sample was comprised of 61 studentsfrom semester II of the Pedagogy Faculty, 31 of them from the control group and the 30 remaining from the experimental group. The survey technique was applied with the help ofa dichotomous questionnaire for the dependent variable. The results were processed using the Mann Whitney U test. The research used the reading of the interactive process reaching the following conclusion: the “active strategies” program has a positive effect on the reading literacy of students from semester II of Pedagogía y Cultura Física (Pedagogy and Physical  Culture) from the University “Enrique Guzmán y Valle”. Regarding the post-test, the value of “z” is above the critical level z < - 1.96 and p = 0.000 lower than α =0.05